The Effect of Soil Type, Water and Organic Materials on the Mechanochemical Destruction of Organic Compounds - Anwar, Ali (Auckland University of Technology, 2011)
Persistent organic pollutants are a well-known threat to the environment. Substances such as polycyclic aromatic hydrocarbons and chlorinated compounds have severely detrimental effects on health for both humans and animals. These toxic organic substances are mainly introduced into soils and groundwater by pesticide use and industrials by products. There is a dire need to develop soil remediation techniques that are efficient, cost effect and relatively uncomplicated. The need is especially great for developing countries that have an obsolete pesticide stockpiles problem. Mechanochemical remediation is an ideal candidate to fill that need. Mechanochemical activation by ball milling was originally developed for mineral processing. It has proved to be an extremely versatile technique and was found to be able to degrade toxic organic compounds. In this study reactive ball milling was used to investigate the destruction rates of naphthalene, chloronaphthalene and diesel in different kinds of soil. Naphthalene, chloronaphthalene and diesel were used as organic pollutant analogues. A GC-MS was used to analyse and quantify the destruction rates. It has been suggested that Total Organic Content (TOC) analysers can also be used to analyse the destruction rates, but a TOC analyser was not available. Quartz had the highest overall destruction rate followed by scoria, limestone, subsoil, greywacke, china clay and terracotta clay. In past studies, it was found that water would hinder destruction efficiencies but no reason as to why or how water did this. This study also looked at why water was reducing destructive capacities of the soils. Water was reacting with the radicals generated by the milling therefore decreasing the total radical available that would react with the target pollutants. The study also looked the effects of organic matter has on the destruction rates of naphthalene. Cellulose powder was added to the sample soils and it was determined that it also decreased the destructive capacities of the soil. The cellulose was sequestering the naphthalene initially, but with continued milling the cellulose and naphthalene were degraded. The effects of ball milling on soil health were also studied. Soil structure and aggregation were altered, but tillage of the milled soil and mixing it with unmilled soil would create healthy aggregation and the sample soils tested were all able to sustain plant life. The study also looked how soil bacteria would react to ball milling. It was determined that the bacteria did not survive the milling process, but milled soils were successfully inoculated by bacteria.
Keywords: Ball milling; Contaminated land; Soil remediation; Mechanochemistry